ANALISIS LAPORAN KEUANGAN PEMERINTAH DAERAH KAB. PADANG PANJANG DAN KAB. MAGELANG TAHUN 2019-2020 - Muhammad Syawal; Br Sembiring, Putri Ramadhani; Sutriana; Hera Sapitri; Aprilia Fauziah (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2024)
Analysis of the financial performance of the Regional Governments of Padang Panjang Regency and Magelang Regency in 2019-2020 was carried out to evaluate differences in budget realization, financial performance ratios, efficiency and financial effectiveness between the two regions. The findings show a significant increase in the effectiveness of local revenue (PAD) in Padang Panjang Regency in 2020, while Magelang Regency recorded a surplus. Analysis of financial efficiency ratios and operational reports also highlights differences in the presentation of Regional Government Financial Reports between the two districts.